The role of the quadriceps muscle in knee extension - Ellis S. Janks (AOSIS, 1983)
In 1949, Smillie proposed that the vastus medialis muscle alone is responsible for the final 10° to 15° of knee extension. A number of more recent studies have proved that the whole quadriceps muscle is responsible for all degrees of knee extension. This evidence is reviewed and the function of the two subdivisions of the vastus medialis is discussed.